Emergency peripartum hysterectomy: Five-year experience in a university hospital - Bayram, Feyza; Urun, Canan; Karakaya, Jale; Karaşin, Süleyman Serkan (Journal of Surgery and Medicine, 2021)
Background/Aim: Postpartum hemorrhage (PPH) is an important cause of maternal death and morbidity worldwide. Its incidence is still increasing in some countries. This study aimed to evaluate the incidence, indications, risk factors, complications, maternal and fetal outcomes, mortality rates and management strategies of emergency peripartum hysterectomy (EPH) in women with life-threatening postpartum hemorrhage. Methods: This retrospective cohort study included 94 cases of EPH performed at tertiary obstetric center between January 2016-January 2021. The demographic data, current pregnancy and delivery mode, hysterectomy indications, operative complications, postoperative conditions, and maternal and fetal outcomes were analyzed. EPH was performed for hemorrhage which cannot be controlled with other conventional treatments within 24 hours of delivery. Results: The incidence of EPH was 1.71 per 1000 deliveries. In our study, the indications of hysterectomy were placenta previa in 47 cases (50%), placental insertion anomalies in 23 cases (24.5%), uterine atony in 22 cases (23.4%), and uterine rupture in 2 cases (2.1%). Hysterectomy was performed after vaginal delivery in 7 patients (7.4%) and during cesarean section in 87 cases (92.6%). Total and subtotal hysterectomy were performed in 88 (93.6%) and 6 cases (6.4%), respectively. Major complications occurred in 40 patients (42.6%). In total, 97.9% of the patients required a transfusion of blood and blood products. The mean postoperative hospital stay was 8.1 (6.1) days. There were two (2.2 %) maternal deaths due to pulmonary embolism and coagulopathy. Conclusion: EPH operation has high maternal morbidity and mortality but is lifesaving when performed at the appropriate time. The most common indication for EPH was placental abnormality (74.5%), followed by uterine atony (23.4%). Together with a significant increase in cesarean rates, significant increases in the frequency of placental abnormalities are remarkable. Limiting the number of cesarean deliveries will have a significant impact on reducing the risk of EPH.